Teaching Classroom Management Subjects Through the Implementation of Assure Model Instructional Design - Yudi Hari Rayanto; Supriyo Supriyo (Universitas Negeri Makassar, 2021)
The aim of this research is to know and find out the practicality of ASSURE Model as one of instructional design implemented in the classroom. This research is taken during Pandemic covid-19 in English Department at PGRI Wiranegara University. From 38 learners, researcher divides the number of learners into 2 classes; they are online and offline class. There are 20 learners as offline class and the rest as online class. The instrument used on this research is questionnaire. During the implementation of ASSURE Model in three meetings, the researcher also requires observers. The involvement of observers is really needed to gain some additional benefit input for making positive revision or suggestion. There are two observers which taken from university lecturer. In gaining data, Researcher distributes similar items of questionnaire both to learners and observers. Based on the result from questionnaire, it is found that ASSURE Model is practical to be implemented both for offline and online class. Although, it is undeniable that there are some problems occur in online class during teaching activity but online class wholly stated that ASSURE Model practically used.